A preliminary study on using Data Envelopment Analysis (DEA) in measuring supply chain efficiency - Wong, Wai Peng; Jaruphongsa, Wikrom; Lee, Loo Hay; Wong, Kuan Yew (Inderscience Publisher, 2007)
This paper illustrates the use of Data Envelopment Analysis (DEA) in measuring supply chain efficiency. Two models were developed – Technical Efficiency (TE) model and Cost Efficiency (CE) model. The information obtained enable managers to identify inefficient operations and take appropriate actions for improvement. The opportunity cost serves as a good reference on resource allocations. The models are further enhanced with scenario analysis to derive more meaningful insights for resources planning. The study proves the usefulness of DEA as a decision-making tool in supply chain. Future research could look into the possibility of modelling DEA in a stochastic supply chain environment.